Perspectives on Development of Measures to Estimate Career Blast Exposure History in Service Members and Veterans - Turner, Stephanie M.; Sloley, Stephanie S.; Bailie, Jason M.; Babakhanyan, Ida; Gregory, Emma (Frontiers in Neurology, 2022)
The Department of Defense (DOD) has recently prioritized the investigation of the acute and chronic adverse brain health and performance effects of low-level blast (LLB) generated by the use of weapons systems. While acute exposure can be quantified by sensor technology, career exposure has no widely accepted and validated measure for characterization. Currently, distinct research groups are developing and validating four promising measures to estimate career blast exposure history: the Salisbury Blast Interview, Blast Exposure Threshold Survey, Blast Ordnance and Occupational Exposure Measure, and the Blast Frequency and Symptom Severity. Each measure offers an assessment of blast history that is uniquely beneficial to addressing specific research questions. However, use of divergent strategies is not efficient to accelerate the field’s understanding of the impact of career exposure and Service-connected health outcomes. As a DOD-wide solution, collaboration across these groups is required to develop a tool(s) that can be standardized across research studies and, ultimately, pared down to be implemented in clinical settings. Here, we overview the current four measures and provide a perspective on the way forward for optimization and/or combination in support of this solution.